The Origin of HIV Aids The best documentary Channel 4 - Sir Emmanuel (NC, 2026)
Vidéo YouTube proposée par Sir Emmanuel. This film doesn't so much delve into the 'origin' of HIV / Aids but it very effectively explains a widely accepted and logical theory.
Droits : Vidéo publique YouTube. Droits conservés par le diffuseur.
Keywords: vidéo; youtube; patrimoine; culture; documentaire; Patrimoine